Allergen-Specific IgA Antibodies Block IgE-Mediated Activation of Mast Cells and Basophils - El Ansari, Yasmeen S.; Kanagaratham, Cynthia; Burton, Oliver T.; Santos, Jenna V.; Hollister, Brianna-Marie A.; Lewis, Owen L.; Renz, Harald; Oettgen, Hans C. (Frontiers in Immunology, 2022)
Mast cells and basophils have long been implicated in the pathogenesis of IgE-mediated hypersensitivity reactions. They express the high-affinity IgE receptor, FcεRI, on their surface. Antigen-induced crosslinking of IgE antibodies bound to that receptor triggers a signaling cascade that results in activation, leading to the release of an array of preformed vasoactive mediators and rapidly synthesized lipids, as well as the de novo production of inflammatory cytokines. In addition to bearing activating receptors like FcRI, these effector cells of allergy express inhibitory ones including FcγR2b, an IgG Fc receptor with a cytosolic inhibitory motif that activates protein tyrosine phosphatases that suppress IgE-mediated activation. We and others have shown that food allergen-specific IgG antibodies strongly induced during the course of oral immunotherapy (OIT), signal via FcR2b to suppress IgE-mediated mast cell and basophil activation triggered by food allergen challenge. However, the potential inhibitory effects of IgA antibodies, which are also produced in response to OIT and are present at high levels at mucosal sites, including the intestine where food allergens are encountered, have not been well studied. Here we uncover an inhibitory function for IgA. We observe that IgA binds mouse bone marrow-derived mast cells (BMMCs) and peritoneal mast cells. Binding to BMMCs is dependent on calcium and sialic acid. We also found that IgA antibodies inhibit IgE-mediated mast cell degranulation in an allergen-specific fashion. Antigen-specific IgA inhibits IgE-mediated mast cell activation early in the signaling cascade, suppressing the phosphorylation of Syk, the proximal protein kinase mediating FcRI signaling, and suppresses mast cell production of cytokines. Furthermore, using basophils from a peanut allergic donor we found that IgA binds to basophils and that activation by exposure to peanuts is effectively suppressed by peanut-specific IgA. We conclude that IgA serves as a regulator of mast cell and basophil degranulation, suggesting a physiologic role for IgA in the maintenance of immune homeostasis at mucosal sites.